From Drug War to Green Rush: the Evolution of Drug Policy in Thailand - Naomi Lin Jialin; Nontakorn Vachiraprasith; Jason Brown (National University of Singapore, 2020)
Thailand became one of the first nations in Asia to legalise medical cannabis in 2019, challenging the region's widespread stance against wider narcotic use including cannabis. The cannabis plant has historically been used medicinally and recreationally in Thailand before being outlawed in many nations an intoxicant. This case covers the state's initial efforts to control cannabis usage in its so-called war on drugs. It lays out the central actors and their considerations in legalising cannabis, including its potential contribution to economic growth and medical treatment advancement; its effect on underground markets and the inmate population imprisoned on drug charges and enforcement efforts to prevent abuses for recreational use. The narrative aims to situate the reader alongside the minds of Thai policymakers at key decision junctures.